Vegetative incompatibility in fungi: From recognition to cell death, whatever does the trick. Issue 4 (October 2016) - Paoletti, Mathieu
Abstract: Allorecognition in fungi takes the form of vegetative incompatibility (VI), a process leading to the programmed cell death of heterokaryotic cells formed after anastomosis between hyphae of genetically incompatible isolates, thereby keeping different genotypes separated. VI is ubiquitous amongst ascomycetes and basidiomycetes, determined by loci named het or vic, and responds to both promoting and limiting selective constraints. While VI has been widely used to analyze fungal populations, genes controlling VI systems have only been characterized at the molecular level in three ascomycete species. VI systems can be considered as having a modular organization, comprised of a polymorphic component for recognition associated with a cell death inducing component often (but not exclusively) including a HET domain protein. However, the actual genes involved differ in sequence and properties. Some VI genes display a patchy phylogenetic distribution, whereas others appear widely conserved in fungal genomes, but their function in controlling VI is restricted to a single or a few related species. It also appears that evolutionary trajectories generating and maintaining polymorphism at these loci differ. Some het genes show low allelic diversity and signs of long term balancing selection and may be specifically selected for allorecognition. Others show high allelic diversity, evidence of positive selection and fast evolution and their products are believed to correspond to immune receptors whose functions have been coopted for allorecognition. Finally, where known, mechanisms for initiating cell death and the cell death reaction itself display similarities and differences between different model species. All these data support the hypothesis that VI is a ubiquitous phenomenon acquired time and time again independently in different fungal lineages.